An Intelligent Three-dimensional Ultrasound Program for Rapidly Imaging of the Fetal Cranial Mid-sagittal Plane - Yi, Yan; Xiong, Yi; X. Zou, Yao; Q. Lin, Mu; Lin, Qi; Jiao, Yang; F. Xu, Jin (Current Medical Imaging, 2016)
This paper described a novel intelligent technique for rapid visualization of the fetal cranial mid-sagittal view to allow for the differentiation of fetal midline anomalies. Two hundred consecutive normal singleton pregnancies and twenty abnormal fetuses with cranial midline anomalies were imaged to display the mid-sagittal view using this new intelligent three-dimensional imaging program developed by our team. The cranial transverse plane was used as starting plane to acquire the threedimensional volumes and then scanned with this new program. The three-dimensional median planes were also evaluated by other two doctors. The reference landmarks of the mid-sagittal plane were that the falxs of fetal head on Plane A and Plane B were parallel to the X-axis and the reference dot was put on the falx. If one doctor thought it was not the median plane or the structure of corpus callosum or cerebellar vermis was not clearly visualized, the case was labelled as failed case. The cranial mid-sagittal view was successfully visualized in 190 normal cases (95%) and 18 abnormal cases (90%) by Smart MSP program. The failed 12 cases becuase the cerebral falxs of these fetuses were unable to be recognized by the program. In conclusion, this new intelligent three-dimensional program is a feasible method for quick visualization of fetal cranial mid-sagittal plane and may become a potential tool for routinely screening the fetal midline anomalies.
Keywords: Congenital anomalies